Consciousness and the Machine - D'Aquili, Eugene G. (Zygon, 1996)
Abstract. We consider only the relationship of consciousness to physical reality, whether physical reality is interpreted as the brain, artificial intelligence, or the universe as a whole. The difficulties with starting the analysis with physical reality on the one hand and with consciousness on the other are delineated. We consider how one may derive from the other. Concepts of universal or pure consciousness versus local or ego consciousness are explored with the possibility that consciousness may be physically creative. We examine whether artificial intelligence can possess consciousness as an extension of the interrelationship between consciousness and the brain or material reality.